Isotope effect in quasi-two-dimensional metal-organic antiferromagnets - Goddard, P; Singleton, J; Maitland, C; Blundell, S; Lancaster, T; Baker, P; McDonald, R; Cox, S; Sengupta, P; Manson, J; Funk, K; Schlueter, J (2008)
Although the isotope effect in superconducting materials is well documented, changes in the magnetic properties of antiferromagnets due to isotopic substitution are seldom discussed and remain poorly understood. This is perhaps surprising given the possible link between the quasi-two-dimensional (Q2D) antiferromagnetic and superconducting phases of the layered cuprates. Here we report the experimental observation of shifts in the Néel temperature and critical magnetic fields (Δ TN / TN ≈4%; Δ Bc / Bc ≈4%) in a Q2D organic molecular antiferromagnet on substitution of hydrogen for deuterium. These compounds are characterized by strong hydrogen bonds through which the dominant superexchange is mediated. We evaluate how the in-plane and interplane exchange energies evolve as the atoms of hydrogen on different ligands are substituted, and suggest a possible mechanism for this effect in terms of the relative exchange efficiency of hydrogen and deuterium bonds. © 2008 The American Physical Society.